(untitled) (Scientific journal of the Fergana State University, 2024)
In this article, the nature and content of the pedagogical activity of a music teacher, the components of the teacher’s activity model: the constructive component, the communicative component, and the organizational component are explained. A description of the skills of a music teacher is also given.